Preparation and spectral properties of mixed-ligand complexes of VO(IV), Ni(II), Zn(II), Pd(II), Cd(II) and Pb(II) with dimethylglyoxime and N-acetylglycine - Shaker S.A. (Hindawi Limited, 2023)
A number of mixed-ligand complexes of the general formula [M(D)(G)] where D=dimethylglyoximato monoanion, G=N-acetylglycinato and M=VO(IV), Ni(II), Zn(II), Pd(II), Cd(II) and Pb(II) were prepared. Each complex was characterized by elemental analysis, determination of metal, infrared spectra, electronic spectra, (1H and 13C) NMR spectra, conductivity and magnetic moments. All these complexes were not soluble in some of the organic solvent but highly soluble in dimethylformamide. The conductivity data showed the non-electrolytic nature of the complexes. The electronic spectra exhibited absorption bands in the visible region caused by the d-d electronic transition such as VO(IV), Ni(II) and Pd(II). The IR and ( 1H, 13C) NMR spectra which have indicate that the dimethylglyoxime was coordinated with the metal ions through the N and O atoms of the oxime group and Nacetylglycine was coordinated with metal ions through the N atom and terminal carboxyl oxygen atom.